PENGEMBANGAN PERANGKAT PEMBELAJARAN PAI DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA SMA - Rosyadi, Mokh Imron (QUALITY, 2019)
The purpose of this study is to develop a PAI learning kit by using the development of the Borg And Gall theory which consists of 10 stages. Data obtained through instruments in the form of observation sheets, interview guides and questionnaires, then analyzed descriptively. Based on a valid judgment decision that the learning tool is declared valid and effective. Proven to increase activity learning and be able to increase students' creative power. The learning tools that have been developed in this study can be used by PAI teachers and can be used as motivation to always develop professional competence, especially in the learning process.